A theory-based evaluation of food waste policy: Evidence from Italy. (October 2019) - Busetti, Simone
Highlights: Bureaucratic simplifications may only have a marginal impact on starting donations. Reputational risks limit donations of food past the best-before-date. Different types of donors present highly diversified reactions to the policy. Policy should not only incentivise donors, but also support food rescue organisations. Theory-based evaluations show how the policy works in practice and help designing future reforms. Abstract: Italy recently reformed its food waste policy by introducing innovative measures, such as the possibility of donating food after the best-before date (BBD) and a significant simplification of the bureaucracy of donations. These measures are advocated by food waste specialists and are thought to increase donations almost automatically. The article performs a theory-based evaluation using the method of realist synthesis to investigate the two measures, test their implicit assumptions, and provide a more complete picture of how the policy works. The results highlight the marginal importance of bureaucratic procedures in the cost structure of donations, the diverse responses of different donors and food rescue organisations, and the importance of considering the capacity and preferences of charities when an increase in donations is expected. Further, the analysis uncovers severe reputational risks that limit both the supply of and demand for food past the BBD, despite legal provisions promoting its donation.